2004
DOI: 10.1111/j.1440-1819.2004.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Factor analysis of Zung Scale scores in a Japanese general population

Abstract: The purpose of the present paper was to investigate the distribution of Zung Self-rating Depression Scale (SDS) scores in a general population and its factor structure. Questionnaires on SDS items were sent to 7136 randomly selected residents aged 20-79 years who lived in districts in Japan with high rates of suicide. Valid responses were received from 5547 residents (response rate: 77.7%). Factor analysis of the SDS scores was conducted. The SDS scores of the male subjects were significantly lower than those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1
5

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 15 publications
1
30
1
5
Order By: Relevance
“…87 It has good internal consistency 38,[137][138][139] and test-retest reliability. 139 Content and criterion validity are good, as it includes most of the DSM-IV criteria for major depression, 140 and concurrent validity is acceptable. 38,141,142 There are a large number of somatic items.…”
Section: Zung Self-rating Depression Scale (Sds) Depression In Non-pdmentioning
confidence: 99%
“…87 It has good internal consistency 38,[137][138][139] and test-retest reliability. 139 Content and criterion validity are good, as it includes most of the DSM-IV criteria for major depression, 140 and concurrent validity is acceptable. 38,141,142 There are a large number of somatic items.…”
Section: Zung Self-rating Depression Scale (Sds) Depression In Non-pdmentioning
confidence: 99%
“…Furthermore, the validity of Zung's Self-rating Depression Scale (SDS) has been demonstrated in several studies 14,15) . This test is sensitive enough to detect depressive symptoms in normal populations 16) . Its Japanese version 17,18) has been ascertained to possess good internal consistency and testretest reliability, and has been used in many research projects such as population surveys 16) .…”
Section: Introductionmentioning
confidence: 99%
“…This test is sensitive enough to detect depressive symptoms in normal populations 16) . Its Japanese version 17,18) has been ascertained to possess good internal consistency and testretest reliability, and has been used in many research projects such as population surveys 16) . In addition, it has been shown that a number of favorable lifestyle practices, including working hours, are associated with the SDS scores 19,20) .…”
Section: Introductionmentioning
confidence: 99%
“…The Japanese version of the SASS was produced by Goto et al, who confirmed that the translated instrument was suitable for evaluating social adaptation in the Japanese population [23]. The SASS has also been validated and found to be easy to use and sensitive to changes in different social functioning areas [24,25]. We have recently reported that a significant negative correlation was obtained between SASS and the Stress and Arousal Check List (SACL), which assesses job stress in healthy workers.…”
Section: Sassmentioning
confidence: 99%